Characterization of Polish Steinernema silvaticum isolates (Nematoda: Steinernematidae) using morphological and molecular data. Issue 3 (17th April 2018) - Lis, M.; Sajnaga, E.; Kreft, A.; Skrzypek, T.; Kazimierczak, W.
Abstract: Four strains of entomopathogenic nematodes were isolated with a live trap method in southern Poland. The isolates were identified as Steinernema silvaticum based on morphological, morphometric and molecular data. Infective juveniles of Polish S. silvaticum isolates differ in body length from S. weiseri (951 vs 740 μm, respectively), and in the hyaline tail portion from S. kraussei (48 vs 38%, respectively). First-generation males of S. silvaticum are longer than those of S. kraussei, S. weiseri and S. ichnusae (1829 vs 1400, 1180 and 1341 μm, respectively). Males of S. silvaticum and a sister species S. kraussei can be distinguished by the distance from the anterior end to the nerve ring (142 vs 105 μm), spicule (66 vs 49 μm) and gubernaculum length (45 vs 33 μm), and the presence of a mucron. The analysis of internal transcribed spacer (ITS), D2-D3 and cox1 sequences of the tested nematodes revealed differences of 3–5%, 3% and 12–13%, respectively, from S. kraussei strains. The phylogeny of both nuclear and mitochondrial genes indicated close relationships of the Polish S. silvaticum isolates with S. kraussei, S. oregonense and S. cholashanense . The reproductive isolation of the studied isolates was confirmed by hybridization tests with other European feltiae–kraussei group representatives. This study has supplemented the original description of S. silvaticum with morphological and morphometric characterization of the first-generation males and females. This is also the first molecular study of this species based on a multi-gene approach.